Propose a New Machine Learning Algorithm based on Cancer Diagnosis - Ali, Mohammed Hasan; Kohbalan, Moorthy; Anad, Mohammed Morad; Mohammed, Mohammed Abdulameer (Institute of Advanced Scientific Research, 2018)
There are many machine learning algorithms proposed for multi-category classification problems in the cancer diagnosis area. Moreover, there are different reasons for using these algorithms such as the ability of machine learning to detect main features from complex data sets, which represents techniques have been utilized as an aim to model the progression and treatment of cancerous conditions. However, the traditional machine learning algorithms are facing several limitations, which may be impacted on the accuracy of classification based cancer diagnosis area. In this review, we focus on the current status of machine learning applications in cancer research, also propose a new algorithm Fast Learning Network to work based on cancer research.